1969
DOI: 10.1192/bjp.115.524.765
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Multiple Sclerosis

Abstract: In previous studies the estimation of the incidence of intellectual changes in multiple sclerosis has varied from as low as 2 per cent. (Cottrell and Wilson, 1926) to as high as 72 per cent. (Ombredane, 1929). In order to establish the incidence accurately, the most satisfactory method would clearly be a long-term follow-up (covering lifetime) of a sample of multiple sclerosis patients. Any cross-sectional study would include patients in varying degrees of advancement of the disease, and patients found to be f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(45 citation statements)
references
References 7 publications
(1 reference statement)
3
42
0
Order By: Relevance
“…The results here presented are in agreement with several reports of normal verbal and visuospatial span 8,10,[12][13][14][22][23][24] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results here presented are in agreement with several reports of normal verbal and visuospatial span 8,10,[12][13][14][22][23][24] .…”
Section: Discussionsupporting
confidence: 93%
“…The WAIS Similarities was found to be impaired by Klonoff et al 8 but not by others 10,14 . Deficits in the WAIS Block Design are not commonly reported.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Neuropsychological disturbances and psychiatric problems are common in multiple sclerosis (MS) [4,12,18,19,23,24]. It is difficult to differentiate which of the disturbances are due to organic disease and which are psychological reactions to a disease that is always an enormous psychological burden, with an unpredictable course and a potential to lead to severe disability and handicap.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed the high incidence of cognitive disturbances in patients with MS (Kahana et al, 1971;Kurtzke et al, 1972;Staples & Lincoln, 1979;Grant et al, 1984;Rao et al, 1984;Filley et al, 1989;Franklin et al, 1990;White, 1990) and it has been suggested that MS be considered a form of "subcortical" dementia, characterized by deficits in visuospatial and memory functions with intact verbal skills (Caine et al, 1986;Rao, 1986). However, other authors have reported also verbal and language loss in MS patients including deficits on the WAIS vocabulary test, naming, reading, and verbal fluency (Diers & Brown, 1950;Jambor, 1969;Ivnik, 1978;Grant et al, 1984;Heaton et al, 1985).…”
Section: To the Editormentioning
confidence: 88%